A simple, cost‐effective, and rapid separation process for the isolation of anticoagulant active fraction from the fruit extract of Momordica charantia: Characterization of bioactive components and anticoagulant mechanism of active fraction in a mouse model. Issue 20 (9th September 2020) - Gogoi, Debananda; Jha, Shambhavi; Chattopadhyay, Pronobesh; Mukherjee, Ashis K.
Abstract: A simple, rapid, and cost‐effective process for the separation of an active anticoagulant fraction from the aqueous fruit extract of Momordica charantia by using rice husk as adsorbed is described. The in vitro anticoagulant activity of active anticoagulant fraction was comparable to commercial anticoagulants heparin and warfarin. Phytochemical analysis revealed the presence of alkaloids, flavonoids, and phytols in the active anticoagulant fraction, nevertheless; it was devoid of glycosides, triterpenoids, tannins, saponins, steroids, and carbohydrates. By gas chromatography with mass spectrometry analysis, decanoic acid, 1, 2, 3‐propanetriyl ester (22.3%), dodecanoic acid, 1, 2, 3‐propanetriyl ester‐d5 (17.3%), dodecenoic acid, 1, 2, 3‐propanetriyl ester (12.5%), and 4‐B‐methylandrostane 2, 3‐diol‐1, 17‐dione (11.4%) were identified as the most abundant constituents of active anticoagulant fraction. Presence of αβ‐fibrinogenase enzyme was identified by biochemical assay but not by liquid chromatography with tandem mass spectrometry analysis suggesting presence of a novel protease enzyme in this fraction. The active anticoagulant fraction demonstrated biding to fibrinogen but not to thrombin or Factor Xa, inhibited the collagen/ADP‐induced mammalian platelet aggregation, showed in vitro thrombolytic activity, noncytotoxic to mammalian cells, showed in vivo plasma defibrinogenation and anticoagulant activities, and inhibited k‐carrageen‐induced thrombus formation in the tails of mice. Therefore, active anticoagulant fraction (an herbal drug) may find therapeutic application for the prevention and/or treatment of hyperfibrinogenemia/thrombosis‐associated cardiovascular disorders.